Synopsis of Diplazium (Polypodiales: Athyriaceae) from Argentina - Arana, Marcelo D.; Mynssen, Claudine M.; Ponce, M. Mónica (Phytotaxa, 2017)
The first treatment of the Argentinian representatives of Diplazium (Athyriaceae) is presented. In the country, the genus is represented by eight species, all of which inhabit the Yungas and Parana rainforests. Identification keys, comments, illustrations, and ecological remarks for the species are presented. Diplazium divergens, D. moccennianum, and D. turgidum constitute novelties for the Argentinian flora. Diplazium divergens occurs in Yungas, and D. moccennianum and D. turgidum in Parana forest. These species are described and illustrated. Diplazium divergens is lectotypified and D. striatum is excluded from Argentinian flora.